Pour un index du droit en vigueur - Le May, Denis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
The purpose of this article is to advocate the realization of a comprehensive Index for Quebec's statutes and regulations. The Index would naturally follow the permanent consolidation now under way but would also be available as an independant research tool. First, the computer-generated text for the establishment of basic data and the time and space limits of the proposed Index is examined. Second, ways of completing and organizing the vocabulary are studied to avoid lapses and render searching easier. The third step proposes the addition of a set of complementary lists such as, for example, local applications, popular titles, time restrictions etc. Finally the author expresses his views on editing, publishing and distributing and concludes with an overall enthusiastic feeling as to the advantages and potential uses of the Index.